Pleurotus highking mushrooms potentiate antiproliferative and antimigratory activity against triple-negative breast cancer cells by suppressing Akt signaling. (November 2020) - Haque, Md. Anwarul; Reza, A. S. M. Ali; Nasrin, Mst. Samima; Rahman, Md. Atiar
In this study, we evaluated the antiproliferative and antimetastatic effects of the Pleurotus highking mushroom on the human triple-negative breast cancer cell lines MDA-MB-231 and HCC-1937 and attempted to elucidate the underlying molecular mechanisms. The antiproliferative effects of P. highking purified fraction-III (PEF-III) were investigated using colony formation and MTS assays. The antimigratory effects of PEF-III were determined by wound healing, transwell migration, and matrigel cell invasion assays. The protein expression levels were evaluated using Western blot analysis. The effect of PEF-III on tumor-sphere formation was examined in a 3D sphere-forming medium, and the mRNA expressions of proliferation- and migration-related genes in the cells from the tumor spheres were determined using RT-qPCR. PEF-III treatment caused a potent and concentration-dependent decrease in the numbers of colonies and viable cells. It also remarkably suppressed the migratory ability of the cells. Mechanistically, PEF-III treatment reduced the expression of pAkt, matrix metallopeptidase-9 (MMP-9), and vimentin. Furthermore, PEF-III reduced the number and size of the tumor spheres in the 3D culture system. It also significantly reduced the mRNA expression of Ki-67, MMP-9, and vimentin in the PEF-III-treated tumor-sphere cells. PEF-III exerted promising antiproliferative and antimigratory effects in triple-negative breast cancer cell lines by suppressing Akt signaling. Therefore, P. highking mushrooms may be considered a potential source for the development of potent anticancer drug(s) for the treatment of breast cancer.